For Multinomial Logistic Regression we can define the Loss Function in the following way:
$J(\theta)=\frac{-1}{m}\sum\limits_{i=1}^m\sum\limits_{j=1}^k 1(y^{(i)}=j)\log(\frac{\exp(\theta_j^{T}x^{(i)})}{\sum\limits_{l=1}^k\exp(\theta_l^{T}x^{(i)})})$
When I am trying to find the derivative of this expression with respect to $\theta$, I have:
$J(\theta)=\frac{-1}{m}\sum\limits_{i=1}^m\sum\limits_{j=1}^k 1(y^{(i)}=j)(x^{i}-x^{i}\frac{\sum\limits_{l=1}^k\exp(\theta_l^{T}x_i)}{\sum\limits_{l=1}^k\exp(\theta_l^{T}x_i)})$
However, this expression is totally incorrect because according to this website: http://ufldl.stanford.edu/wiki/index.php/Softmax_Regression I should get:
Nevertheless, I do not understand at all how he obtained this result. Do you know which steps the teacher followed in order to find this result ?
Thank you so much for your help